The role of electron microscopy in kidney lesions: A review of its diagnostic importance (Journal of Pathology of Nepal, 2013)
Electron microscopy is a technology which was at one time widely used for renal as well as non-renal benign and malignant diseases, but its use has been rapidly declining as hospitals all over the world cut down on expenses. This leaves the renal pathologist with only light microscopy and immunofl uorescence at his disposal to diagnose diseases. Few studies have stated the importance of electron microscopy in routine renal biopsy reporting. We look at different cases where electron microscopy has been helpful in diagnosis and review the literature to assess the role this investigative modality still has to play in modern renal pathology. Journal of Pathology of Nepal (2013) Vol. 3, No.1, Issue 5, 411-415 DOI: http://dx.doi.org/10.3126/jpn.v3i5.7871